Occurrence of insomnia and daytime somnolence among professional drivers - Wolińska, Weronika; Tatol, Piotr; Zdziarski, Krzysztof; Karpeta-Pawlak, Iwona Ewa; Mroczek, Bożena (Family Medicine & Primary Care Review, 2017)
Background . Insomnia is described as an insufficient amount or quality of sleep that lasts for at least a month. Sleeplessness in the group of professional drivers may lead to accidents and other road incidences. Factors influencing the work of drivers include their work time – the amount of time they spend driving their vehicle. Objectives . The aim of the study was to estimate the frequency of the occurrence of insomnia among professional drivers, taking into consideration daytime sleepiness, socio-demographic variables and hourly work organization. Material and methods. Study was conducted on 94 professional drivers from the Zachodniopomorskie region: 25 (26.60%) paramedics, 24 (25.53%) police officers, 23 (24.47%) fire fighter drivers and 23 (24.47%) truck drivers. A questionnaire was used with the following components: Athens Insomnia Scale (AIS ), Epworth Sleepiness Scale (ESS ) and an original questionnaire containing questions regarding socio-demographic data and health behaviors. Results . Insomnia was diagnosed in 12 professional drivers (12.77%). Among them the majority were truck drivers – 4 respondents (4.26%). A relationship between the age of respondents and occurrence of insomnia measured with the AIS scale was found. A relationship between insomnia and drivers posing a threat to road traffic was also found (χ2 = 19.95; p = 0.005). People suffering from moderate daytime sleepiness are 35 years old on average. Conclusions . Drivers older than 35 and those with BMI above 28 are groups with the highest risk of suffering from insomnia. Drivers with insomnia more frequently pose a threat to road traffic. Drinking coffee has no impact on insomnia and daytime sleepiness.